Furfural Produces Dose-Dependent Attenuating Effects on Ethanol-Induced Toxicity in the Liver - Cheng, Zhuo; Luo, Xuanmei; Zhu, Zixin; Huang, Yonghui; Yan, Xiue (Frontiers in Pharmacology, 2022)
Background: Alcohol-associated liver disease (ALD) increases the health burden worldwide, but effective drugs to prevent ALD are lacking. Furfural is a small molecule that can limit alcohol production in microorganisms and may have the capacity to attenuate ethanol-induced toxicity. Methods: Human HepG2 cells were incubated with ethanol and furfural, and cell viability, NAD+/NADH ratio, and mitochondrial function assays were performed. RNA sequencing (RNA-seq) data were used to annotate enriched pathways, and these findings were confirmed by reverse transcription-quantitative PCR (RT–qPCR) and Western blotting. C57BL/6J mice were fed a Lieber-DeCarli liquid diet. After 4 weeks, biochemical analysis of mouse serum and histological analysis of mouse livers were performed. Results: Different concentrations of furfural exerted different effects on mitochondria: low-dose furfural reduced reactive oxygen species (ROS) production, maintained mitochondrial transmembrane potential, and inhibited apoptosis pathway activation, while high-dose furfural led to the opposite effects. In mice, furfural mitigated transaminase increases and attenuated the lipid metabolism disorder that had been induced by ethanol. Conclusion: Low-dose furfural reduced ethanol-induced toxicity in the liver. Consuming food or beverages containing the appropriate level of furfural when drinking alcohol may be a convenient and useful way to prevent ALD.